1992
DOI: 10.4319/lo.1992.37.7.1447
|View full text |Cite
|
Sign up to set email alerts
|

Isotope fractionation associated with ammonium uptake by a marine bacterium

Abstract: Bacteria can account for a large fraction of total NH,' uptake in both pelagic and benthic marine environments. 15N natural abundance was examined to understand the effect of NH,' uptake by bacteria on nitrogen isotope biogeochemistry. Isotope fractionation (E) for NH,' uptake by the marine bacterium Vibrio harveyi changed from -4 to -277~ when cells were grown on 23-l 82 PM NH,+ and then from -27 to -14Ya when the NH;' concentration increased to 23.3 mM. Changes in fractionation correlated with a switch in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
179
0
1

Year Published

2003
2003
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 214 publications
(195 citation statements)
references
References 34 publications
(37 reference statements)
9
179
0
1
Order By: Relevance
“…In the later stages of growth, the reaction may become diffusion limited (R diff oR AMO ) and the isotope effect for diffusion ( 15 e diff ) would dominate. A similar mechanism has been examined for variations in expressed isotopic fractionation during NH 4 þ assimilation by bacteria (Hoch et al, 1992) and marine algae (Pennock et al, 1996), as well as CO 2 uptake by algae (Laws et al, 1997) and plants (O'Leary, 1981). Diffusion of NH 3 in aqueous solution is estimated to have an isotope effect of 20% (Hoch et al, 1992), which is similar to the late-stage 15 e NH3 values we observed.…”
Section: Nitrogen Isotopic Fractionationsupporting
confidence: 56%
See 2 more Smart Citations
“…In the later stages of growth, the reaction may become diffusion limited (R diff oR AMO ) and the isotope effect for diffusion ( 15 e diff ) would dominate. A similar mechanism has been examined for variations in expressed isotopic fractionation during NH 4 þ assimilation by bacteria (Hoch et al, 1992) and marine algae (Pennock et al, 1996), as well as CO 2 uptake by algae (Laws et al, 1997) and plants (O'Leary, 1981). Diffusion of NH 3 in aqueous solution is estimated to have an isotope effect of 20% (Hoch et al, 1992), which is similar to the late-stage 15 e NH3 values we observed.…”
Section: Nitrogen Isotopic Fractionationsupporting
confidence: 56%
“…This was particularly apparent for CN25 and CN75 enrichments grown at low [NH 4 þ ] (o20 mM), which exhibited a considerable lag phase before the commencement of ammonia oxidation. Variable e values have been observed in many other organisms, including denitrifiers (Granger et al, 2008), methane oxidizers (Templeton et al, 2006), sulfate reducers (Habicht et al, 2005) and nitrite oxidizers (Casciotti, 2009;Buchwald and Casciotti, 2010), and during assimilation of NH 4 þ by heterotrophic bacteria (Hoch et al, 1992) but has not previously been reported in ammonia-oxidizing organisms. We explore two hypotheses that could explain a large apparent isotope effect at the early stages of growth (Figure 6).…”
Section: Nitrogen Isotopic Fractionationmentioning
confidence: 99%
See 1 more Smart Citation
“…Ammonification can be abiotic and is just included for completeness. Metal catalysts and isotopic fractionations are taken from the literature (Brunner et al, 2013;Buick, 2007a;Casciotti, 2009;Godfrey and Glass, 2011;Hoch et al, 1992;McCready et al, 1983;Nishizawa et al, 2014;Pennock et al, 1996;Waser et al, 1998;Zerkle et al, 2008;Zhang et al, 2014 Tian et al (2011) and Zahnle (1986), 10. Schoonen & Xu (2001), 11.…”
Section: Resultsmentioning
confidence: 99%
“…Non-quantitative NH 4 + assimilation imparts a fractionation of up to -27‰ when [NH 4 + ] > 20 μM, but the fractionation decreases to -4‰ at lower concentrations (Hoch et al, 1992;Pennock et al, 1996;Waser et al, 1998). Under NH 4 + replete conditions one may thus expect light biomass in underlying sediments (i.e.…”
Section: A Primer On Nitrogen Isotopes In Geological Samplesmentioning
confidence: 99%